Pleural effusion in a patient with metastatic gastrointestinal stromal tumor treated with imatinib: case report. (December 2014) - Bongiovanni, Alberto; Ricci, Marianna; Riva, Nada; Calpona, Sebastiano; Oboldi, Devil; Pieri, Federica; Cavaliere, Davide; Mercatali, Laura; Liverani, Chiara; La Manna, Federico; De Vita, Alessandro; Foca, Flavia; et al.
ABSTRACT : Gastrointestinal stromal tumors are rare malignancies characterized by c-kit and PDGFR-α mutations targeted by imatinib. Pleural effusion is a very rare side effect of imatinib treatment. A 65-year-old female with metastatic gastrointestinal stromal tumor developed electrolyte imbalance, severe peripheral edema and progressively worsening dyspnea 2 months after starting imatinib. Having excluded cardiovascular and pulmonary disorders, imatinib was discontinued and prednisone 25 mg orally daily was begun. The patient's condition improved substantially over the next 48 h with a progressive decrease in dyspnea and a reduction in pleural effusion and peripheral edema. All side effects had resolved within 1 month. In view of the partial response obtained, the patient re-started imatinib after a 1-week interruption. Prednisone was maintained and there was no further toxicity.